لطائف لغوية: دراسة تطبيقية في سورة التوبة - بلال، محمد الحسن مختار; حسن، أحمد عثمان فضيل (جامعة الإمام المهدي, 2017)
تهدف هذه الدراسة إلى الكشف عن بعض اللطائف اللغوية في سورة التوبة، وذلك من خلال خمسة محاور رئيسة هي: المحور الصوتي، والمحور الدلالي، والمحور التركيبي، والمحور النحوي، والمحور البياني. استخدم الباحثان المنهج الوصفي التحليلي باعتباره المنهج المناسب للإيفاء بمتطلبات الدراسة، ومن أهم النتائج التي توصل إليها الباحثان في هذه الدراسة إن بعض الظواهر النحوية لها أثر في تحديد دلالة الكلمات في النص القرآني، كما أن العلماء القدامى والمحدثين لم ينكروا الجانب الدلالي في هذه الأصوات المتجاورة في تحقيق بعض المعاني الدلالية، وقد أوصى الباحثان بعدد من التوصيات أهمها، ضرورة وضع الأسس والقواعد التي تضبط الاجتهاد في بيان اللطائف اللغوية في القرآن، والإسهام في إعداد علماء وباحثين لدراسة المسائل العلمية، والحقائق الكونية؛ في ضوء ما ثبت في القرآن والسنة. The study aims to reveal some of the features of linguistic miraculization in the Holy Qura’n in Tawba Chapter through four main areas, which are: the structural, the semantic, the phonological and the grammatical aspects. The researchers used the descriptive analytical approach as the most suitable method to answer the questions in the study. The most important findings of the study were that some phonological phenomena have determining role on the semantic aspect of sounds, the words in sentences, and Qura'nic verses in this study. Moreover, the old and later scholars did not reject the semantic aspect of these adjacent sounds in the realization of particular semantic meanings. Accordingly, the researchers provide a number of recommendations the most important of which are: the necessity of establishing the criteria and rules that govern innovative interpretation of the scientific miraculization in the Qura’n and; the need for contributions to train scholars and researchers to study the scientific issues and the universal truths in accordance to what has been testified by the Qura’n and the Sunnah as well as encouraging universities to give support and opportunities in postgraduate registration and grants in the area of the scientific miracles within the Holy Qura’n and the Sunnah
Keywords: الإعجاز القرآني -- الفصاحة اللغوية -- التحليل اللغوي -- سورة التوبة -- اللغة العربية